Sustentabilidad de los sistemas agroforestales de café de la Asociación Agroartesanal de Pequeños Productores de Café Especial del cantón Loja - Sánchez Castillo, Marco Antonio (2023)
Sustainability is understood as a harmonious development between economic development and environmental conservation to satisfy current needs without compromising the necessary resources for future generations. This research allowed to characterize and evaluate the sustainability of the Agroforestry Systems (SAF) of small producers of special coffee in the Loja canton, Ecuador. In order to determine if this activity is socially, economically and environmentally sustainable, information on variables on the family nucleus was collected; the specific environmental, social and economic conditions of SAFs. Based on Sarandón and Flores methodology, environmental, economic and socio-cultural indicators were generated to estimate the General Sustainability Index (IsGen). The results of the Clúster analysis showed the grouping of four types of producers with similar characteristics. The most representative variables for this analysis are control of burning, fertilizing activities, management of stubble from temporary crops, use of coffee husks, and soil conservation actions used by producers. The determination of Sustainability estimated an IsGen of 2.38; Within this, the ecological dimension reached a value of 2.58; while the economic dimensions 2.75 and socio-cultural 1.82. Through these indices it was established that the SAFs are not sustainable, the environmental and economic dimensions turned out to be positive and strong; nevertheless, the sociocultural dimension is limiting. Keywords: agroforestry systems, coffee producers, indicators, dimensions, General Sustainability Index, IsGen.